Old players with a newly defined function: Fra-1 and c-Fos support growth of human malignant breast tumors by activating membrane biogenesis at the cytoplasm - Motrich, Ruben Dario (2013)
A shared characteristic of tumor cells is their exacerbated growth. Consequently, tumor cells demand high rates of phospholipid synthesis required for membrane biogenesis to support their growth. c-Fos, in addition to its AP-1 transcription factor activity, is the only protein known up to date that is capable of activating lipid synthesis in normal and brain tumor tissue. For this latter activity, c-Fos associates to the endoplasmic reticulum (ER) through its N-terminal domain and activates phospholipid synthesis, an event that requires it Basic Domain (BD) (aa 139-159). Fra-1, another member of the FOS family of proteins, is over-expressed in human breast cancer cells and its BD is highly homologous to that of c-Fos with two conservative substitutions in its basic amino acids. Consequently, herein we examined if Fra-1 and/or c-Fos participate in growth of breast cancer cells by activating phospholipid synthesis as found previously for c-Fos in brain tumors. We found both Fra-1 and c-Fos over-expressed in more than 95% of human ductal breast carcinoma biopsies examined contrasting with the very low or undetectable levels in normal tissue. Furthermore, both proteins associate to the ER and activate phospholipid synthesis in cultured MCF7 and MDA-MB231 breast cancer cells and in human breast cancer samples. Stripping tumor membranes of Fra-1 and c-Fos prior to assaying their lipid synthesis capacity in vitro results in nonactivated lipid synthesis levels that are restored to their initial activated state by addition of Fra-1 and/or c-Fos to the assays. In MDA-MB231 cells primed to proliferate, blocking Fra-1 and c-Fos with neutralizing antibodies blocks lipid-synthesis activation and cells do not proliferate. Taken together, these results disclose the cytoplasmic activity of Fra-1 and c-Fos as potential targets for controlling growth of breast carcinomas by decreasing the rate of membrane biogenesis required for growth.